Implementasi Computational Thinking pada pembelajaran PAI di SMA N 1 Gondang - Fuanny Rossyita Widyawati; Hafidz Hafidz (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
One of the skills that must be possessed by every individual in the 21st century is problem solving skills or what is known as Computational Thinking. Computational Thinking is a thinking process to solve complex problems based on computer science. In this approach there are four indications of Computational Thinking, namely decomposition, pattern recognition, abstract, algorithms. The purpose of this study is to describe the implementation of Computational Thinkingand describe the inhibiting factors and driving factors of the application problem solving with the CT approach. This research is field research. The method used was qualitative with a phenomenological. The research location is at SMA N 1 Gondang, Gondang District, Sragen Regency. Collecting data using observation techniques, interviews and documentation. With subject waka curriculum, PAI teachers and class X students. Research used source triangulation and technique triangulation as a test of data validty. Data analysis techniques include data reduction, presentation data and verication of conclusions. Based on the result of the discussion, that the implementation Computational Thinking in class X students in PAI learning still needs direction and stimulus guidance in solving problems considering that class X is a trasition from junior high school to high school level. The supporting factors are adequate school facilities and infrastructure and teacher strategies in stimulating critical thinking in solving problems. Besides that, the inhibiting factorsinclude the passivity of some students in discussions and the characteristics of students in different ways of thinking in solving problems.